Geoelectrical images of normal fault zones: tectonophysical interpretation of the shallow-depth electrical resistivity tomography data on the Buguldeika-Chernorud graben in the Western Baikal region - K. Zh. Seminsky; A. A. Bobrov (Геодинамика и тектонофизика)
In the study of normal fault zones located in the central Baikal rift, a new approach was applied to process and interpret the shallow-depth electrical resistivity tomography data. This approach is based on the concepts of tectonophysics and considers three-stage formation of a fault and the corresponding three degrees of rock material disturbance, which are regularly detected in the rock mass. The degrees are established by statistical analysis of specific electrical resistance (SER) measured from the electrical resistivity tomography profile across the faults under study. Based on a geoelectrical profile, it is possible to identify the sites wherein the disturbed rocks show the indicators of the early, late and final stages of faulting. The profile provides the basis for specifying the boundaries of the fault zone and the main features of its internal structure. The tectonophysical approach was applied to study a series of normal fault zones varying in ranks. The zones are located on the sides of the Buguldeika-Chernorud graben located near the Olkhon Island in the Western Baikal region. By comparing the geoelectrical profiles constructed under the same methodology, it was established that the near-fault anomalies of electrical resistance are qualitatively similar. Their structure is defined by the general mechanism of normal faulting in the upper crust during sliding along a curved (listric) fault plane. The research results are consolidated in an idealized geoelectrical model: a 2D profile showing a low-resistance anomaly that corresponds to a normal fault zone. This anomaly is asymmetrical and mushroom-shaped, and its internal structure is heterogeneous. In the lying wing of the fault, the anomaly reflects the fan-shaped set of secondary faults caused by the subvertical movements in the normal fault zone, which surface is steeply inclined to the horizon. In the hanging wing, the structure of the anomaly reflects a system of lens-like grabens that form above the surface of the main fault plane that becomes less inclined with depth. The structure of the geoelectrical model proposed for the Olkhon region follows the general regularities controlling formation of listric-shaped normal fault zones. This model can be widely used for diagnostics of tectonic settings and crustal extension structures in other regions.